Automation and Skill Shift: Understanding the Workplace Transformation - Rahmadina, Tasya (Journal of Sustainability Industrial Engineering and Management System, 2024)
This study explores the evolving dynamics of workforce transformation amid accelerating automation and the ensuing shift in skill demands. In an era characterized by rapid technological advancement, automation is redefining not only job roles but also the parameters of employability across industries. The research adopts a qualitative, literature-based methodology grounded in interpretive analysis to examine the socio-technical implications of automation on the nature of work, particularly the emergence of new skill requirements and organizational adaptation strategies. By reviewing and synthesizing insights from approximately 60 scholarly sources published between 2010 and 2024, the study employs thematic content analysis to identify patterns related to job reconfiguration, skill shifts, and institutional responses. The findings reveal that automation primarily restructures rather than replaces jobs, reallocating routine tasks to machines while intensifying the cognitive and emotional demands placed on human workers. Moreover, the study underscores the growing importance of digital literacy, emotional intelligence, adaptability, and continuous learning as essential competencies in the modern workplace. Institutional readiness—manifested through policy reform, educational innovation, and proactive organizational strategy—is found to be a critical determinant of whether automation leads to empowerment or displacement. The research concludes that sustainable workforce transformation requires an integrated, human-centered approach that aligns technological deployment with inclusive and adaptive systems of education and employment. This study contributes to the broader discourse by offering a nuanced, context-sensitive understanding of how automation is currently reshaping labor markets, while advocating for ethical and inclusive frameworks to guide future transitions.